Portable Electrochemical System for the Monitoring of Biogenic Amines in Soil as Indicators in Assessment of the Stress in Plant - Lucian-Gabriel Zamfir; Maria Lorena Jinga; Roxana Tulea; Gaudențiu Vărzaru; Mariana Constantin; Iuliana Răut; Cristina Firincă; Maria-Luiza Jecu; Mihaela Doni; Ana-Maria Gurban (Chemistry Proceedings)
Highly sensitive electrochemical biosensors for biogenic amine (BA) detection were developed using commercial screen-printed electrodes (SPEs) modified with a nanomaterial based on single-walled carbon nanotubes (SWCNT) and redox mediator, Prussian Blue (PB) and amine oxidase enzymes. The nanocomposite material enables an enhancement of the analytical performances for hydrogen peroxide detection, which represents the byproduct of the enzymatic oxidation of the BAs. The developed biosensors were integrated with a miniaturized potentiostate and a wireless data transfer interface in a portable system. The system was used for the detection of polyamines in soil solutions collected with a low-volume suction lysimeter.